Design and Simulation of Scanning Probe Micro-Cantilever for the Scanning Probe Lithography - Dang, Van Hieu; Le, Van Tam; Nguyen, Van Duong; Chu, Manh Hoang; Dang, Van Hieu (Old Journal, 2019)
In this paper, we report on design and simulation of a scanning probe micro-cantilever. The micro-cantilever consists of a sharp silicon tip integrated at the free end of the silicon fixed-free beam. The micro-cantilever is driven electrostatically using parallel plate capacitive-type actuation. The sharp silicon tip is in pyramidal shape, which is created by the anisotropic etching of single-crystal silicon in potassium hydroxide. An electrode is spaced upper the back side of the cantilever with an air gap to form the capacitive-type actuation. The operation characteristics of the scanning probe micro-cantilever are simulated by finite element method. We study the displacement of the tip and the variation of capacitance depending on applied voltage. The operation of the cantilever in air environment is also investigated. The micro-cantilever is designed for application in the scanning probe lithography.